Differential reaction of citrus species in Malaysia to huanglongbing (HLB) disease using grafting method - Shokrollah, Hajivand; Abdullah, Thohirah Lee; Sijam, Kamaruzaman; Abdullah, Siti Nor Akmar; Abdullah, Nur Ashikin Psyquay (Science Publications, 2009)
Problem statement: Huanglongbing (HLB) is a phloem limited disease in citrus caused by a fastidious bacterium called 'Candidatus Liberibacter' found in Africa, Asia and United States of America (USA). HLB can severely reduce vigor and yield or kill all citrus trees within 5 years. There is a need to screen and identify suitable rootstock for propagation of clean plan materials for citrus in the tropics. This study was conducted to detect the presence of HLB on 18 selected citrus species and to categorize the level of infection and susceptibility of citrus species to HLB. Approach: Eighteen citrus species were assessed for susceptibility to HLB by graft transmission from source infection (Citrus reticulata). Results HLB was detected in 15 species 6 months after grafting using PCR test. Conclusion: The species could be categorized in five groups: Severe group (72-58% severity) which includes C. reticulata, C. sinensis, C. reshni cv. cleopatra, moderate group (50-41% severity) includes Fortunella sp. cv. Kasturi Chinai, C. macrophylla, C. microcarpa, mild group (25-17% severity) which included C. medica, C. aurantifolia, Citrus sp. (natural biotype), C. jambhiri. The tolerant group which did not show any HLB symptoms but tested positive by PCR test includes C. aurantium and C. aurantifolia. The resistant groups which include C. grandis cv. Limau Bali, C. hysterix and Citrus sp. cv. Limau Tembikai showed no symptoms and were tested negative for HLB.